Do Technologies Influence Indirect the Sustainable Urban Transport in Developing Countries? A Mediating Roles of Infrastructure, Vehicles, and Operations in Tanzania - Samson, Sesera; Shatta, Deus N. (Journal of Industrial Engineering & Management Research, 2026)
Increasing mobility demand and rapid urbanization in developing countries have intensified environmental degradation, congestion, traffic inefficiencies, and unsustainable transport practices. Although technological innovations such as digital platforms. intelligent transport systems, and smart mobility solutions are encouraged as remedies, empirical evidence clearing up how these technologies translate into sustainable urban transport outcomes remains limited. In specific, inadequate attention has been given to the mediating role of transport systems (infrastructure, vehicles, and operations) in linking technology adoption to sustainability of urban transport. This study therefore examined the influence of technology on sustainable urban transport, emphasizing infrastructure, vehicles, and operations as mediating constructs. The study adopted positivism research paradigm and an explanatory research design to test hypothesized causal relationships. A stratified sampling technique was employed to obtain a sample of 300 respondents drawn from key urban transport stakeholders. Data were collected through documentary review and structured questionnaires to enhance contextual reliability and validity. Descriptive statistics data were computed using IBM SPSS Statistics Version 26 to analyze respondents’ demographic characteristics while Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 was used to assess both measurement and structural models in inferential data analysis. The results show that technology adoption significantly influences indirectly sustainable urban transport. Furthermore, transport systems particularly infrastructure modernization partially mediates this relationship, strengthening sustainability outcomes. The study reveals new insights to the existing body of knowledge by providing empirical evidence that technology alone is insufficient; its influence on sustainable urban transport depends on the effectiveness of transport system integration. The findings offer managerial and policy implications for urban transport authorities and planners seeking to promote sustainable urban transport in developing countries, Tanzania in particular.